Is helping always the preferred decision? Preschool- and elementary school-aged children's helping decisions in complex social situations - Schuhmacher, Nils; Rack, Natalie; Beckmann, Lena; Kärtner, Joscha (Frontiers in Developmental Psychology, 2023)
Helping is usually perceived as a positive behavior, but it can also have negative side effects. Moreover, helping decisions are often embedded in complex social situations that can create social dilemmas for children and adults, such as the decision whether or not to help a friend steal. However, based on previous research, it remains unclear how young children decide in such complex social situations and how their decisions differ between preschool- and elementary school age. Therefore, in the present study, we investigated the moral decisions of 4- to 8-year-old children in complex social situations (N = 152 children; 69 girls; all European, urban and middle-class). In a 2 × 2 design, each child was asked whether a story protagonist should help or not help in four different conditions, namely helping a friend or a stranger to get their own object (i.e., moral conditions), or helping a friend or a stranger to take someone else's object (i.e., immoral conditions). We found that children clearly approve of helping in moral conditions and generally disapprove of helping in immoral conditions. We also found that older children were more likely to disapprove of helping in immoral conditions. Furthermore, children preferred helping friends to helping strangers only in moral but not in immoral conditions. Taken together, these findings suggest that children's decisions to help undergo significant changes from preschool to elementary school, as they are further qualified by criteria such as respecting the rights of others and avoiding harmful consequences of helping for third parties.